The Cambridge handbook of social representations - Sammut, Gordon; Andreouli, Eleni; Gaskell, George; Valsiner, Jaan (Cambridge handbooks in psychology, 2015)
"A social representations approach offers an empirical utility for addressing myriad social concerns such as social order, ecological sustainability, national identity, racism, religious communities, the public understanding of science, health and social marketing. The core aspects of social representations theory have been debated over many years and some still remain widely misunderstood. This handbook provides an overview of these core aspects and brings together theoretical strands and developments in the theory, some of which have become pillars in the social sciences in their own right. Academics and students in the social sciences working with concepts and methods such as social identity, discursive psychology, positioning theory, semiotics, attitudes, risk perception and social values will find this an invaluable resource."--Back cover.